2020
DOI: 10.3390/rs12081287
|View full text |Cite
|
Sign up to set email alerts
|

Computer Vision and Deep Learning Techniques for the Analysis of Drone-Acquired Forest Images, a Transfer Learning Study

Abstract: Unmanned Aerial Vehicles (UAV) are becoming an essential tool for evaluating the status and the changes in forest ecosystems. This is especially important in Japan due to the sheer magnitude and complexity of the forest area, made up mostly of natural mixed broadleaf deciduous forests. Additionally, Deep Learning (DL) is becoming more popular for forestry applications because it allows for the inclusion of expert human knowledge into the automatic image processing pipeline. In this paper we study and quantify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…In this study, DNNs were used to locate and identify the six classes that are defined in Section 2.3 , with a focus set on the blueberry class. The basis for this deep learning approach is described in previous studies [ 20 , 43 ], which led to the use of the algorithms that are described in this section.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, DNNs were used to locate and identify the six classes that are defined in Section 2.3 , with a focus set on the blueberry class. The basis for this deep learning approach is described in previous studies [ 20 , 43 ], which led to the use of the algorithms that are described in this section.…”
Section: Methodsmentioning
confidence: 99%
“…is needed to capture all of the possible image variabilities. However, as proven by our previous work [ 20 , 43 ], transfer learning is a useful tool for image analysis applications, where the training dataset is too small to properly train these feature extractors from scratch.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results showed that the highest accuracy of trunks and leaves based on transfer learning was improved by 51.38% and 51.69%, respectively, compared with the accuracy of ordinary deep learning. In 2020, Kentsch et al conducted research on classification identification of a winter orthomosaic dataset by ResNet-50 based on transfer learning [16]. The results showed that from no transfer learning to transfer learning from a general-purpose dataset, the accuracy with a 9.78% improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional image is an important carrier of information in multimedia, and 70% of the information people obtained by comes from the visual system [4], [5]. However, an effective processing method is urgently needed because of the large amount of digital image data and considerable storage space [6]- [8].…”
Section: Introductionmentioning
confidence: 99%